Effectiveness of oral health education intervention among 9–12-year-old school children - Pipiet Okti Kusumastiwi; Alfini Octavia (Berita Kedokteran Masyarakat, 2026)
Purpose: This study evaluated the effectiveness of a school-based oral health education (OHE) program in improving oral hygiene knowledge, attitudes, and practices (KAP), as well as plaque control and gingival health, among elementary school students in Yogyakarta, Indonesia. Methods: A randomized controlled trial was conducted involving 202 students aged 9 to 12 years. The intervention group received a 30-minute OHE session with reinforcements at the third and sixth months, while the control group received no initial education. Outcomes were measured using a validated KAP questionnaire and clinical indices, including the Plaque Index (PI), Gingival Index (GI), and Decayed, Missing, and Filled Teeth (DMFT) scores at baseline, three months, and six months. Results: All participants completed the six-month follow-up. Baseline characteristics between groups were comparable (p > 0.05). The intervention group showed significant improvements in knowledge, attitude, and practice scores at 3 and 6 months compared with the control group (p < 0.001). Significant reductions in plaque and gingival index scores were also observed in the intervention arm, whereas the control group demonstrated minimal changes. DMFT scores remained statistically unchanged in both groups. Conclusion: Changes in DMFT scores were not statistically significant in either group. These findings suggest that a structured, repeated school-based OHE program can effectively promote oral health behavior and improve periodontal status in children. The results support integrating regular oral health education into the primary school curriculum as a sustainable approach to preventing oral disease in developing-country settings.